2023
DOI: 10.3390/cancers15143689
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PARP7 Increases Type I Interferon Signaling in EO771 Breast Cancer Cells and Prevents Mammary Tumor Growth by Increasing Antitumor Immunity

Marit Rasmussen,
Karoline Alvik,
Vinicius Kannen
et al.

Abstract: PARP7 is a member of the ADP-ribosyltransferase diphtheria toxin-like (ARTD) family and acts as a repressor of type I interferon (IFN) signaling. PARP7 inhibition causes tumor regression by enhancing antitumor immunity, which is dependent on the stimulator of interferon genes (STING) pathway, TANK-binding kinase 1 (TBK1) activity, and cytotoxic CD8+ T cells. To better understand PARP7′s role in cancer, we generated and characterized PARP7 knockout (Parp7KO) EO771 mouse mammary cancer cells in vitro and in a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…The mixture was quenched with cool water (150 mL) at room temperature and extracted with EtOAc (100 mL × 3). The combined organic layers were washed brine (20 General Procedure for the Preparation of 9g−9h. Methyl 6-(4-Iodo-1H-pyrazol-1-yl)hexanoate (32a).…”
Section: S)-n-(6-(hydroxyamino)-6-oxohexyl)-2-(4-(3-(2-((6-oxo-5-(tri...mentioning
confidence: 99%
See 2 more Smart Citations
“…The mixture was quenched with cool water (150 mL) at room temperature and extracted with EtOAc (100 mL × 3). The combined organic layers were washed brine (20 General Procedure for the Preparation of 9g−9h. Methyl 6-(4-Iodo-1H-pyrazol-1-yl)hexanoate (32a).…”
Section: S)-n-(6-(hydroxyamino)-6-oxohexyl)-2-(4-(3-(2-((6-oxo-5-(tri...mentioning
confidence: 99%
“…18,19 Recently, PARP7 was confirmed to involve in cytosolic NA sensing and multiple viral RNA infections through repressing IFN-I signaling. 2,20 Mechanistically, when viral infection takes place, PARP7 inhibits the autophosphorylation of TBK1 by MARylate TBK1, which is essential for the activation of TBK1 and type I interferon response and anticancer immunity. 21,22 Some studies have shown that inhibitors of PARP7 induce IFN-I signaling in mouse colorectal cancer (CT-26) cells and human lung adenocarcinoma (NCI-H1373) cells in an immune cell-dependent manner, which leads to tumor cell death in vivo.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The evidence from mouse experiments further supports the potential of utilizing PARP7 inhibitors as targeted agents for cancer therapy. 23 PARP12, a member of the PARP family, is also a monoPARP that plays a crucial role in regulating cell survival and regulating cell regeneration. 24 Notably, emerging evidence suggests that targeting PARP12 holds promise as a novel approach to alleviate the resistance of breast cancer cells to genotoxic stress.…”
Section: Introductionmentioning
confidence: 99%
“…PARP7 (TIPARP) was originally identified as a gene that is strongly upregulated by ligands of aryl hydrocarbon receptor (AHR) and PARP7 MARylate AHR to negatively regulate the transcriptional activity of AHR . Recently, studies have shown that inhibition of PARP7 could restore type I interferon (IFN) signaling responses and might activate the immune system to prevent tumor escape. , RBN-2397 ( 1 , Figure ), an oral PARP7 inhibitor (PARP7i) developed by Ribon Therapeutics Inc., is the first PARP7 inhibitor to enter clinical study. It is currently being investigated in combination with anti-PD-1 antibody pembrolizumab for squamous cell carcinoma of the lung (SCCL) .…”
Section: Introductionmentioning
confidence: 99%